Dzieciństwo jako wartość - Piecuch, Ewelina (Karkonoska Państwowa Szkoła Wyższa, 2011)
The article encompasses the problems of childhood and its influence on the rest of one's life. I have concentrated on this crucial and specific time in life. It is demonstrated by biology, medicine, psychology, and psychoanalysis that human habits are formed in childhood. Health, hygiene and aesthetic behaviour determine one's further fate and influence life in its entirety. It is that phase of human life that determines the rest of it. In childhood children manifest their cognitive and emotional powers. They are ready to discover the world. That is how they demonstrate their power, but also fragility and sensitivity.
Keywords: childhood; values; children